Internalizing Character Education Values through the Biography of KH Ahmad Dahlan in Islamic Primary Education - Mochammad Nginwanun Likullil Mahamid; Febry Fabian Susanto; Najah Baroud; Moh. Buny Andaru Bahy (Journal of Contemporary Islamic Primary Education, 2026)
This study aims to analyze the internalization of character education values through the biography of KH Ahmad Dahlan in learning processes at the Elementary School/Islamic Elementary School. This research employs a qualitative approach using a library research method, focusing on the analysis of the figure’s biography and its relevance to strengthening character education within the context of contemporary Islamic education. The findings indicate that KH Ahmad Dahlan’s biography embodies several key character values, including religiosity, social awareness, a spirit of reform (tajdid), and rational thinking. These values demonstrate strong relevance for internalization in Islamic elementary school learning processes through various strategies, such as storytelling methods, integration into the Islamic Religious Education curriculum, and habituation in daily school activities. Therefore, the biography of Islamic figures serves not only as a source of historical knowledge but also as an effective medium for shaping students’ character from an early age. This study contributes to the development of a contextual and applicable history-based character education model in Islamic primary education.